1969
DOI: 10.12669/pjms.322.8850
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic manifestation of congenital transverse amputation of autopod in Pakistani subjects

Abstract: Terminal transverse deficiency of forearm is a very rare limb malformation. Most of the cases have traumatic etiology and congenital presentation is less common. A series of six individuals with transverse deficiency through the hands is presented in this communication. The cases were congenital, morphologically similar and showed loss of four fingers, most often postaxial. The affected arm was reduced in size compared to the contralateral limb and there was distortion of palmer creases. All cases were sporadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…However, in this case, the questions above did not befall according her. Although there are various suspicion about the causes of hemimelia, some authors state that its etiology is unknown (Macrí et al, 2009;Pisoni et al, 2012;Peres et al, 2013;Macrí et al, 2014), including in humans (Riaz et al, 2016). In this case, the presence of consanguinity, as reported by the owner, can be considered as a possible cause of dysostosis, in accordance with Prats (2005).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, in this case, the questions above did not befall according her. Although there are various suspicion about the causes of hemimelia, some authors state that its etiology is unknown (Macrí et al, 2009;Pisoni et al, 2012;Peres et al, 2013;Macrí et al, 2014), including in humans (Riaz et al, 2016). In this case, the presence of consanguinity, as reported by the owner, can be considered as a possible cause of dysostosis, in accordance with Prats (2005).…”
Section: Discussionsupporting
confidence: 66%
“…In general, the fetal anomalies can be a result of an unbalanced diet during the pregnancy, drug administration or viral infections (Johnson, Kenneth and Watson, 2014;Riaz et al, 2016). However, the etiology of hemimelia is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Based mainly on convenience sampling, this study is a pilot attempt to estimate the prevalence of limb defects in the adult population. There are no published data available that can indicate the spectrum of limb anomalies in RYK, although a few case studies of specific disease types have been published [ 18 , 19 ]. Nationwide health surveys are regularly conducted in many countries to update the existing disease prevalence, assess their impact on society, and identify demographic correlates and risk factors [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to rarity, this group of malformations has not gained much attention among the researchers. 16,17 Few epidemiological studies published from Pakistan have revealed that CLD constitute a sizable group among the limb anomalies in certain Pakistani populations. [18][19][20][21] The aim of the current study was to document the prevalence pattern, phenotypic manifestations, and descriptive genetic profile of CLD in a cohort of patients from the North Western region of Pakistan.…”
Section: Introductionmentioning
confidence: 99%